Infrastructure and tools of financial monitoring to counter shadow income receipts. (Journal of Economic Research & Business Administration, 2015)
The article deals with the scientific tools to counteract legalization processes and money laundering of the shadow economy in Kazakhstan and in other countries around the world. Effective financial monitoring system as a system of risk of money laundering neutralization requires close collaboration between all authorized structures, both at the national and at the international level. Financial monitoring infrastructure on prevention of legalization ( laundering) of illegally obtained incomes and the financing of terrorism is discussed in the article. In general, to develop a commonstrategy and coordination for financial monitoring the structure of financial monitoring is considered, starting with international organizations against legalization of illegally and ending with the Department for Financial Monitoring in major cities of Kazakhstan and the entity ‘s compliance – control in banks.
Keywords: infrastructure; tools; financial monitoring; money laundering; international organization; compliance monitoring